Lesional Temporal Lobe Epilepsy: Does the “Uncommon” Differ from the Common? - Ashutosh Kumar; Suyash Singh; Anant Mehrotra; Lily Pal; Shweta Katiyar; Nandita Chaudhary; Pawan Kumar Verma; Ved Prakash Maurya; Kuntal K. Das; Jayesh Sardhara; Kamlesh Singh Bhaisora; Arun Kumar Srivastava; et al. (Indian Journal of Neurosurgery)
Objectives This study aims to evaluate the subgroup consisting of uncommon pathological entities presenting with temporal lobe epilepsy (TLE). Methodology Twenty-four consecutively operated patients of lesional temporal lobe epilepsy were included in the study. Eleven cases were identified that had pathologies implicated as “uncommon” in previously done studies on the pathology of TLE. A subgroup analysis consisting of these uncommon lesions was done for clinical presentation and seizure outcome. The seizure outcome was assessed in terms of Engel and International League Against Epilepsy (ILAE) classification. Results Nine different pathological entities were identified within the study group. The mean age at surgery was 18.6 years (range 2–30 years). The mean duration of epilepsy was 48.3 months and the average duration of follow-up was 39.2months. All patients had seizures as the only complaint except three. Three patients had focal-aware seizures, two had focal motor onset, and the rest all had focal-unaware seizures. Seven patients were seizure free and the average age at diagnosis for these patients was 15.4 years (range 2–24 years.). The duration of seizure in the postoperative seizure-free group was 29.7 months and it was 81 months for the other group. All the patients with persistent postoperative seizures had focal-unaware seizures preoperatively. Conclusion Despite the small and heterogeneous nature of this subgroup of uncommon lesions causing temporal lobe epilepsy, the clinical presentation, prognostic factors, and seizure outcome are similar to the cohort of common pathologies, including mesial temporal sclerosis.